Kinematic assessment of women’s gait in high-heeledshoes - Zostawa, Paweł; Uścinowicz, Natalia; Klich, Sebastian; Zostawa, Jacek (European Journal of Clinical and Experimental Medicine, 2014)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction. Statistically, among 60 percent of women of age between 20-23, a disorder in the locomotor system, especially in the case of feet, can be observed. Women who frequently walk in a high-heeled footwear are at a much higher risk of overstraining their locomotor systems, than women who wear flat-sole shoes. The aim of the work was the assessment of the biokinematic parameters of metatarsal and phalangeal joints, as well as of the top ankle joints among women who walk in a high-heeled footwear. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. The research was carried out on 43 women being 22±2,1 years old. The examined group consisted of women who declared to regularly walk in a high-heeled footwear. The control group included women who sporadically walk in this type of shoes. In order to carry out the research, the motion analysis system BTS Smart-E and the modified protocol (Heyes-Davis), which took into account the angle in metatarsal and phalangeal joints and in the top ankle joint, were used. The measurements were conducted without the footwear. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. The angular value in the statistical examination (P1) in metatarsal and phalangeal joints amounted to 153,3o (group A) and 152,3o (group B), whereas at the moment of the first contact of a heel with the ground - (P2)149,4o and 149,4o (p<0,05). Upon the contact of the head of metatarsal (P3), the angle value amounted to 176,1o , whereas in the control group – 168,6o (p<0,05). Upon the toe’s contact with the ground (P4), the angle amounted to 176,5o and 169,2 (p<0,05). At the moment when there was no contact with the ground (P5), the values amounted respectively to: group A – 150,5o , and for group B – 138,7o (p<0,05). <p class="rtejustify" style="box-sizing: border-box; margin: 0px; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusions. Walking in a high-heeled footwear for an extended amount of time results in permanent changes in gait kinetics, which was demonstrated through the decrease in the extension angle values in metatarsal and phalangeal joints, as well as through the increase in the top ankle joints